A Nonpolar Blueberry Fraction Blunts NADPH Oxidase Activation in Neuronal Cells Exposed to Tumor Necrosis Factor-α. (13th March 2012) - Gustafson, Sally J.; Dunlap, Kriya L.; McGill, Colin M.; Kuhn, Thomas B.
Abstract : Inflammation and oxidative stress are key to the progressive neuronal degeneration common to chronic pathologies, traumatic injuries, and aging processes in the CNS. The proinflammatory cytokine tumor necrosis factor-alpha (TNF- α ) orchestrates cellular stress by stimulating the production and release of neurotoxic mediators including reactive oxygen species (ROS). NADPH oxidases (NOX), ubiquitously expressed in all cells, have recently emerged as pivotal ROS sources in aging and disease. We demonstrated the presence of potent NOX inhibitors in wild Alaska bog blueberries partitioning discretely into a nonpolar fraction with minimal antioxidant capacity and largely devoid of polyphenols. Incubation of SH-SY5Y human neuroblastoma cells with nonpolar blueberry fractions obstructed the coalescing of lipid rafts into large domains disrupting NOX assembly therein and abolishing ROS production characteristic for TNF- α exposure. These findings illuminate nutrition-derived lipid raft modulation as a novel therapeutic approach to blunt inflammatory and oxidative stress in the aging or diseased CNS.